Causality of unsaturated fatty acids and psoriasis a Mendelian randomization study - Li, Junchen; Shen, Qian; Guo, Chenqi; Wang, Yingdong; Ma, Yuxiao; Zhang, Yu (Frontiers in Nutrition, 2024)
Background: Many observational studies have identified a link between unsaturated fatty acids and psoriasis. However, they contain reverse causality and confounding factors, and there is no definite causal study between unsaturated fatty acids and psoriasis. Objectives: Analysis of causality between unsaturated fatty acids and psoriasis by Mendelian randomization. Methods: We used IEU Open GWAS Project, omega-3 PUFA and omega-6 PUFA data from 114,999 subjects, MUFA data from 13,535 subjects, and psoriasis data from 4510 cases and 212,242 controls were included. We employed the inverse-variance weighted (IVW) method as the primary analytical approach and four additional MR methods. Moreover, we performed heterogeneity and horizontal pleiotropy assessments using Cochrane's Q and MR-Egger intercept tests, respectively. Finally, we performed sensitivity analyses to enhance our findings' precision and veracity. Results: IVW results showed no causal effect of omega-3 PUFA on psoriasis (p = 0.334; OR, 0.909; 95% CI, 0.748–1.104), omega-6 PUFA cause psoriasis (p = 0.046; OR, 1.174; 95% CI, 1.003–1.374), MUFA cause psoriasis (p = 0.032; OR, 1.218; 95% CI, 1.018–1.457), no causal effect of omega-3 PUFA in psoriasis (p = 0.695; OR, 0.989; 95% CI, 0.937–1.044), no causal effect of omega-6 PUFA in psoriasis (p = 0.643; OR, 1.013; 95% CI, 0.960–1.068), psoriasis is not causal to MUFA (p = 0.986; OR, 1.000; 95% CI, 0.949–1.055). Heterogeneity, horizontal pleiotropy, and sensitivity analyses showed reliable results. Conclusions: We found that circulating omega-6 PUFA and MUFA cause psoriasis, while omega-3 PUFA do not. Treatments that lower circulating omega-6 PUFA and MUFA are effective in psoriasis. After a better understanding of fatty acid intake and circulation, the population can be advised to regulate their diet.